Transgenic rat models for mutagenesis and carcinogenesis. (December 2017) - Nohmi, Takehiko; Masumura, Kenichi; Toyoda-Hokaiwado, Naomi
Abstract Rats are a standard experimental animal for cancer bioassay and toxicological research for chemicals. Although the genetic analyses were behind mice, rats have been more frequently used for toxicological research than mice. This is partly because they live longer than mice and induce a wider variety of tumors, which are morphologically similar to those in humans. The body mass is larger than mice, which enables to take samples from organs for studies on pharmacokinetics or toxicokinetics. In addition, there are a number of chemicals that exhibit marked species differences in the carcinogenicity. These compounds are carcinogenic in rats but not in mice. Such examples are aflatoxin B1 and tamoxifen, both are carcinogenic to humans. Therefore, negative mutagenic/carcinogenic responses in mice do not guarantee that the chemical is not mutagenic/carcinogenic to rats or perhaps to humans. To facilitate research on in vivo mutagenesis and carcinogenesis, several transgenic rat models have been established. In general, the transgenic rats for mutagenesis are treated with chemicals longer than transgenic mice for more exact examination of the relationship between mutagenesis and carcinogenesis. Transgenic rat models for carcinogenesis are engineered mostly to understand mechanisms underlying chemical carcinogenesis. Here, we review papers dealing with the transgenic rat models for mutagenesis and carcinogenesis, and discuss the future perspective.